(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article examines the state of ensuring food safety based on the processing industry in our country. In particular, the classification of the participants of the innovation cluster of the food industry and their mutual relations, the classification of the general necessary relations between the innovation clusters of the food industry and the main factors was analyzed. The experiences of foreign countries in the development of food safety industry policy were studied, and the model of ensuring food safety based on the innovative development of food industry clusters and directions for further development of the network were proposed.